Health and safety statistics highlights 2002/03 - UK. Health and Safety Commission (Sudbury, 2003)
"Health and Safety Statistics Highlights 2002/03 presents the latest top level statistics on workplace fatalities and injuries, and work-related ill health in Great Britain, with links to more detailed information."